THE APPLICATION OF TECHNOLOGY IN MUSEUMS - Peni Zulandari Suroto; Made Handijaya Dewantara; Aulia Ardista Wiradarmo (Pusat Penelitian dan Pengabdian kepada Masyarakat (P3M) Politeknik Negeri Bali, 2020)
Alongside with collections in form of historical objects, as well as objects related to human culture, museums have taken an important role in providing education, especially for tourists who visiting a destination. However, at its conditions who have lack of innovation, has implications for declining number in interest of tourists to come and dig deeper into the collections in museum. This research set an objective to answer how could technology applied in museum. Research has been done through Focus Group Discussion (FGD) and depth observation conducted on January 2020, in Jakarta. Nine informants/participants involved during FGD, including 5 museums (public and private), 2 technology providers, and 1 museum users community. Research indicates that strong cooperation between museums and technology providers has been elaborated, in particular in several museums in Jakarta. Augmented Reality and Virtual Reality are two most applications applied. Meanwhile, museums have established several platforms for security and data collection purposes. Both parties will try to add more platforms through video mapping application, projection mapping, virtual tour, and internet of things (IoT) operations. Process of increasing experience and immersion encounters obstacles, to provide additional experience to visitors, so that all five senses that exist in visitors, can enjoy all museum collection. Technology could embrace interaction and immersion to add more experience value on visitors. Thus, tourism industry would be more attractive with the presences of museums.